"It's Going to be Extra Fun!": Analysis of an Atypical Case of Teen Homicide as Leisure Behavior1. Issue 6 (23rd April 2018) - Williams, D J; Vincent, Jolene
Abstract: Recently, scholars in literary criminology and leisure sciences have begun to explore the role of broader leisure culture in potentially shaping fantasy development, planning, preparation, and execution in specific cases of expressive homicide. This brief report focuses on an unusual case of expressive homicide, wherein two teen offenders in Idaho collaborated to murder a female classmate as an intentional leisure activity. Prior to the murder, the offenders created a videotape describing how they planned to commit this (and additional) murders. A careful analysis of the videotape content, along with other primary court documents, illustrates how leisure preferences can combine with traditional psychiatric variables to shape the unique process of certain forms of expressive homicide.